The effects of walking intervention on preventing neck pain in office workers: A randomized controlled trial - Sitthipornvorakul, Ekalak (J Occup Health, 2019)
OBJECTIVE: This study aimed to evaluate the efficacy of increased daily walking steps on the 6‐month incidence of neck pain among office workers. METHODS: Healthy office workers with high risk of neck pain were recruited into a 6‐month prospective cluster‐randomized controlled trial. Participants were randomly assigned at the cluster level, into either intervention (n = 50) or control (n = 41) groups. Participants in the intervention group were instructed to increase their daily walking steps to a designated level for a duration of 6 months. Participants in the control group received no intervention. The outcome measures included the 6‐month incidence of neck pain as well as its pain intensity and disability level. Analyses were performed using multivariable logistic regression model. RESULTS: Of the participants in the intervention and control groups, 22% and 34% reported a 6‐month incidence of neck pain, respectively. After adjusting for confounders, a significant preventive effect of walking intervention was found (adjusted odd ratio 0.22, 95% confidence interval 0.06‐0.75). No significant difference in pain intensity and disability level was found between those in the intervention and control groups. CONCLUSION: An intervention to increase daily walking steps reduced onset neck pain in high‐risk office workers. However, the walking interventions did not decrease pain intensity and disability in those increasing the number of daily walking steps compared to the control group.